Development of the PreAnestesiApp application for perioperative risk estimation in adults. - Rincón-Valenzuela, David A.; María Vélez, Karina (Colombian Journal of Anesthesiology / Revista Colombiana de Anestesiología)
Introduction Preoperative assessment is fundamental in perioperative medicine, as inadequate evaluation and insufficient patient preparation can increase the risk of anesthetic complications. In Colombia, there are currently no interoperable preoperative clinical information systems that integrate cognitive aids and support for decision-making. Objective The objective of this project was to develop a functional prototype of an application that integrates perioperative risk estimation and cognitive aids for entering information in the electronic medical record during preoperative assessment in adults. Methods To develop the PreAnestesiApp application software, the spiral model was used in six iterative phases: 1) requirements definition, 2) design, 3) development, 4) testing and integration, 5) implementation, and 6) operation. Results The project enabled the development of a functional prototype of PreAnestesiApp, an application software that integrates perioperative risk estimation and cognitive aids to prompt documentation in the electronic medical record during preoperative assessment in adults. Since its implementation in October 2013 until December 2023, PreAnestesiApp has been used in five healthcare institutions, where more than 171,000 preoperative assessments have been performed. Conclusions PreAnestesiApp is an application software designed to assist in perioperative risk estimation in adults, with potential use in perioperative medicine education.